Dexmedetomidine as a Cardioprotector in Cardiac Surgery (Review) - I. A. Kozlov; T. V. Klypa; I. O. Antonov (Общая реаниматология, 2017)
The literature review presents an analysis of publications on the use of a selective α2-adrenergic receptor agonist (α2-AR) dexmedetomidine as a cardioprotector in cardiosurgical interventions. It summarizes historical aspects of the introduction of α2-AR agonists in the intensive care practice. It analyzes possible mechanisms of the cardioprotective effect of dexmedetomidine (central sympatholysis, favorable effects on the coronary circulation and relief of the coronary steal syndrome in originally ischemized areas of the myocardium, antiinflammatory and antioxidant effects, and prevention of apoptosis activation). Data from experimental studies of dexmedetomidine cardioprotection were analyzed. Results of clinical studies, including data of metanalyses, were discussed. It dwells on data on the favorable effect of dexmedetomidine on various parameters of the postoperative period, including a decreased risk of delirium, general complications of cardiosurgical interventions, and the mortality rate in patients. It presents data on cardioprotective properties of dexmedetomidine in surgical patients who undergo noncardiac interventions, particularly vascular ones, including high risk surgeries in the aorta. A comparative analysis of results of clinical trials studying the dexmedetomidine cardioprotection during surgeries with extracorporeal circulation was performed. A range of pharmacological effects of dexmedetomidine during anesthesiological support of cardiac surgeries, including those in elderly and senile patients, was described. It has been concluded that the dexmedetomidine cardioprotection in the various fields of surgery is obviously very promising.